Harmonização tributária: uma análise comparativa entre a União Europeia e as dificuldades vivenciadas pelo Mercosul no que concerne à tributação indireta sobre o consumo - Ramos, Pablo Alessandro de Guimarães (2024)
This dissertation aimed to discuss the possibility of tax harmonization in MERCOSUR. To this end, it researches tax harmonization, its developments and relevant conditions for tax harmonization to take effect; discusses the problems generated by the lack of harmonization in MERCOSUR; and exposes the instruments that can be used to correct problems generated by the lack of harmonization. Regarding the methodology, regarding its objective, this is a descriptive-analytical research. Regarding the data source, this is predominantly bibliographic and documentary research, considering that doctrines, legislation and jurisprudential understandings that are dedicated to understanding tax harmonization were researched. It was seen that by creating more consistent and predictable tax rules, tax harmonization can improve predictability for companies and investors, making it possible for them to make business-related decisions with greater legal certainty. However, it is clear that fiscal harmonization in MERCOSUR faces important challenges, including differences in tax systems and the economic priorities of each member country. Additionally, harmonization does not necessarily mean the imposition of a uniform tax system, but rather the search for a common balance that can meet the interests and needs of member countries. At the end of the study, it was concluded that progress towards tax harmonization in MERCOSUR is a complex task and requires planning in negotiations and agreements between member countries. However, this harmonization is seen as an important means of promoting economic integration and creating a more favorable environment for trade and investment in the region and, as seen throughout this dissertation, significant difficulties will have to be faced.